Impact of harvesting cleaner fish for salmonid aquaculture assessed from replicated coastal marine protected areas. Issue 4 (21st April 2017) - Halvorsen, Kim Tallaksen; Larsen, Torkel; Sørdalen, Tonje Knutsen; Vøllestad, Leif Asbjørn; Knutsen, Halvor; Olsen, Esben Moland
ABSTRACT: Wrasse (Labridae) fisheries have increased markedly in Norway since 2010. Wrasse are being used as cleaner fish in salmonid aquaculture to control sea-lice infestations. However, fundamental knowledge on the demography and abundance of the targeted wrasse populations in Norwegian waters is lacking, and the consequences of harvesting at the current intensity have not been assessed. Here, we compared catch per unit effort (CPUE), size, age and sex ratio of goldsinny wrasse ( Ctenolabrus rupestris ) and corkwing wrasse ( Symphodus melops ) between marine protected areas (MPAs) and control areas open for fishing at four localities on the Skagerrak coast in Southern Norway. The CPUE of goldsinny larger than the minimum size limit was 33–65% higher within MPAs, while for corkwing three of four MPAs had higher CPUE with the relative difference between MPAs and control areas ranging from −16% to 92%. Moreover, corkwing, but not goldsinny, was significantly older and larger within MPAs than in control areas. Sex ratios did not differ between MPAs and control areas for either species. Our study suggests that despite its short history, the wrasse fisheries have considerable impacts on the target populations and, further, that small MPAs hold promise as a management tool for maintaining natural population sizes and size structure. Goldsinny, being a smaller-sized species, also seems to benefit from the traditional minimum size limit management tool, which applies outside MPAs.